Development of adjustable fluid damper device for the bridges subjected to traffic loads. (January 2023) - Farahpour, Hengameh; Hejazi, Farzad
Abstract: In this research, an Adjustable Bypass Fluid Damper (ABFD) is developed by utilizing a pair of external fluid flow pipes and flow control valves. The flow control valves control the flow pressure of the fluid passing through bypass pipes and adjusted the function of the fluid damper to limit the displacement of the structure within the allowable range. Therefore, the function of the fluid damper device is adjustable according to the displacement of the structure. The ABFD device is developed through implementing an adjustable valve in bypass pipes that able to change and adjust the flow and pressure of the oil inside the viscous damper during movement of piston under applied vibrations and control the resultant damping and resistance force of the damper device. Therefore, through the new proposed design, the action of viscous damper has been changed from passive control device to an adjustable system which is capable to function as an device with different capacities and also able to change the response from a damping device to a restrainer system. The analytical model of the proposed ABFD device is developed and the performance of the device has been formulated according to the control valve position. Then the finite volume model of the moving fluid inside the device has been developed and the function of the device was evaluated through Computational Fluid Dynamics analysis. In the next step, the prototype of ABFD has been fabricated and experimental tests have been conducted using a dynamic actuator to evaluate the performance of the device in various control valve conditions. The numerical analysis and experimental test results for the ABFD prototype revealed that the developed device is capable of developing a wide range of damping levels and there is a desirable agreement between numerical predictions and experimental results. Thereafter, to examine the effect of the application of the ABFD device in the bridge structures, the proposed ABFD device was implemented in the 19/5 California overcrossing bridge. The considered bridge equipped with an ABFD device is modeled using the finite element method and it's subjected to the passing vehicle loadings. The results showed that the bridge's response is dramatically improved with the implementation of the six ABFD dampers and the peak displacement of the structure reduces by 35 percent while the control valves are half-open.